Severe Thrombocytopenia in the Third Trimester of Pregnancy Subsequent to Seasonal Non-H1N1 Influenza A Virus Infection. Issue 5 (September 2016) - Curtis, Samantha; Carlan, Stephen; Busowski, John; Busowski, Mary; Musa, Faisal
Abstract : Background: Viral infections can induce hematological disorders including immune thrombocytopenic purpura (ITP). Influenza-induced ITP is infrequent and has never been reported in a third-trimester pregnant woman. Case: A previously healthy pregnant woman in the third trimester presented with non-H1N1 Influenza A and a platelet count of 0. She was diagnosed with ITP and treated with intravenous immunoglobulin and oseltamivir. Her platelet count returned to normal by day 8, and she delivered vaginally a normal infant who had no evidence of thrombocytopenia or Influenza. Conclusions: Influenza A can induce secondary ITP in pregnancy, and the standard treatment for both ITP and Influenza A is effective.